Age-dependent changes in 24-hour rhythms of thymic and circulating growth hormone and adrenocorticotropin in rats injected with freund's adjuvant - Esquifino, Ana I. (2001)
Objective: To analyze the 24-hour changes in thymic and serum concentration of growth hormone (GH) and adrenocorticotropin (ACTH) and their correlation with thymic concentrations of glutamate, aspartate, taurine and GABA in young and old rats during the acute phase of adjuvant's arthritis. Methods: Young (50-day-old) and old (18-month-old) rats were injected subcutaneously with Freund's adjuvant or its vehicle (paraffin oil containing 15% mannide monooleate). Eighteen days later, they were killed at six different time intervals throughout a 24-hour cycle. Serum and thymic levels of GH and ACTH were measured by radioimmunoassay. Thymic amino acid concentration was measured by HPLC. A quantitative assessment of arthritis was made in an independent group of rats by plethysmography. Results: Old rats injected with Freund's adjuvant exhibited fewer clinical signs of inflammation than young rats. Significant 24-hour changes in thymic and serum GH occurred, except for serum GH in adjuvant's vehicle-treated old rats. Aging augmented thymic GH and decreased serum GH. Immunization with Freund's adjuvant did not modify GH concentration. Thymic and serum concentration of GH correlated negatively. Thymic ACTH varied significantly over 24 h with maxima during the dark phase, except in Freund's adjuvant-treated young rats. Maximal serum ACTH levels occurred in the late afternoon except in Freund's adjuvant-treated old rats which showed maxima at night. Immunization with Freund's adjuvant augmented thymic and circulating concentrations of ACTH. Thymic and serum concentration of ACTH correlated positively. Thymic concentration of glutamate, aspartate and taurine decreased in aged rats and correlated significantly with thymic ACTH. Conclusion: The results support the existence of a thymic compartment of GH and ACTH that may be independently regulated.